2013
DOI: 10.1158/1078-0432.ccr-13-1320
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study of an Agonist CD40 Monoclonal Antibody (CP-870,893) in Combination with Gemcitabine in Patients with Advanced Pancreatic Ductal Adenocarcinoma

Abstract: Purpose This phase I study investigated the maximum-tolerated dose (MTD), safety, pharmacodynamics, immunological correlatives, and anti-tumor activity of CP-870,893, an agonist CD40 antibody, when administered in combination with gemcitabine in patients with advanced pancreatic ductal adenocarcinoma (PDA). Experimental Design Twenty-two patients with chemotherapy-naïve advanced PDA were treated with 1000 mg/m2 gemcitabine once weekly for 3 weeks with infusion of CP-870,893 at 0.1 mg/kg or 0.2 mg/kg on day 3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
284
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 396 publications
(300 citation statements)
references
References 27 publications
8
284
0
Order By: Relevance
“…Prior clinical trials of single-agent agonistic CD40 mAb, or CD40 mAb in combination with chemotherapy, have demonstrated clinical activity. 7,1113,15,21 In a previous trial, 4 patients among 15 with advanced melanoma had a PR to a single dose of the CD40 mAb CP-870,893. 7 Potential synergy of CD40 activation and CTLA-4 blockade has been established in mouse tumor models, 6 but this study is the first to test this hypothesis in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Prior clinical trials of single-agent agonistic CD40 mAb, or CD40 mAb in combination with chemotherapy, have demonstrated clinical activity. 7,1113,15,21 In a previous trial, 4 patients among 15 with advanced melanoma had a PR to a single dose of the CD40 mAb CP-870,893. 7 Potential synergy of CD40 activation and CTLA-4 blockade has been established in mouse tumor models, 6 but this study is the first to test this hypothesis in patients.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 A second strategy would be to formally explore the potential of immunologic approaches such as CD40 agonists and T-cell engineering strategies. 9,10 Such strategies fit nicely with the current emphasis on understanding the unique role of the local host response to pancreatic cancer, and preclinical studies suggesting that the prolific stroma associated with pancreatic cancer serve as a barrier to the distribution of cytotoxic chemotherapy into the pancreatic primary tumor. 3,11,12 The extent to which a stromal barrier function can be targeted in metastatic pancreatic cancer is currently being addressed in trials using stromal disrupting agents in combination with chemotherapy.…”
mentioning
confidence: 90%
“…They further showed that the tumor regression was mediated by macrophage that facilitated the depletion of tumor stroma. CP-870, 893, a monoclonal antibody, is a CD40 agonist that was evaluated in combination with gemcitabine in a phase I trial in patients with advanced PDA (33). Four of twentytwo patients (18%) achieved partial response.…”
Section: Immune Cellsmentioning
confidence: 99%